Plasma Metabolomic and Intestinal Microbial Analyses of Patients With Severe Aplastic Anemia - Shao, Yuanyuan; Qi, Weiwei; Zhang, Xiaomei; Ran, Ningyuan; Liu, Chunyan; Fu, Rong; Shao, Zonghong (Frontiers in Cell and Developmental Biology, 2021)
Aplastic anemia is a bone marrow failure disease caused by autoimmune abnormality,but the pathogenesis that trigger the immune mechanism of severe aplastic anemia (SAA) are not clear.To look for potential metabolic markers and pathogenesis mechanisms in SAA，we investigated the microbial metabolomics and metabolomics in SAA patients and healthy controls. SAA patients had increased number of Enterobacteriales and Lactobacillales, while had decreased Bacteroidales, Clostridiales and Erysipelotrichales compared to healthy controls at the order level. Eight metabolites were significantly different between SAA group and healthy control group. Coumaric acid, L-phenylalanine and sulfate were up-regulated in SAA group, L-glutamic gamma-semialdehyde, heobromine, 3a, 7a-dihydroxy-5b-cholestane, Gamm-delta-Dioxovaleric acid, 9, 10-DHOME were down-regulated. We tested seven short-chain fatty acids (SCFAs) in the serum of SAA patients and healthy controls. We found that butyrate was down-regulated in SAA group, isobutyrate and isovalerate were up-regulated. In conclusion, Microbial metabolomics and metabolomics are altered in SAA patients. It might be potential molecular mechanisms which trigger the immune imbalance of SAA.